Supporting employee well-being: The case of independent restaurants. Issue 2 (4th March 2021) - Gordon, Susan; Parikh, Anish
ABSTRACT: Employees who feel supported by their organizations and managers tend to have higher well-being and job satisfaction and lower turnover. High turnover is a challenge for the restaurant industry and independent restaurants often do not have the same resources as chain restaurants to support employees and thus retain employees. The purpose of this study was to uncover specific support mechanisms employed by managers of independent restaurants. Restaurant employees and managers were interviewed regarding the types of organizational and management support they receive and provide. Results produced 17 support mechanisms within four main themes of: human resources practices, leadership practices, work atmosphere, and well-being. Based on the framework produced, implications for academia and industry include actions and behaviors restaurant managers can engage in to help employees feel more supported. Some of these actions are scheduling flexibility, confidentiality of employee issues, transparency of business decisions, and solicitation of feedback.